Transformative state publics. Issue 3 (2nd July 2016) - Cooper, Davina
Abstract: Against the conventional assumption that publics, and particularly radical publics, are outside the state, this article explores their mutual combination and entanglement in order to consider how states might contribute to progressive politics. At the heart of this account is a concept of the state that incorporates the dissident and fleeting, and a conception of transformative publics based on four modalities: prefigurative, improper, liberatory, and unconditional. Transformative publics can be found within state formations; they also combine with them to produce new political governance relations. To develop this argument, the article focuses on two kinds of publics: those involving compelled state actors, such as school children and prisoners; and those, such as protest camps, taking shape through grass-roots political action.